Evaluation of Serum IL-6 and FABP Levels in Acute Kidney Injury (AKI) Patients Following Cardiac Catheterization - Hind F. Aref; Nazar A. Naji; Hadaf D. Ibrahim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Acute kidney damage is a severe condition common in patients who have undergone heart surgery(catheterization) and secondary injury is also referred to as being synonymous with surgery. The goal ofthis research is to determine the rate ofinterleukin-6 (IL-6) and fatty acid-related protein (FABP) in patientswith acute renal injury (AKI) following cardiac catheterization. The study is performed on (81) patients (64males and 17 females) aged 40-75 years. Data from most patients are reported in the form of age, genderand smoking background questionnaire. The results indicate a significant increase in serum levels of IL-6and FABP in patients with severe renal insufficiency after cardiac catheterization by (79%) males versus(21%) females. In this study, improved risk prediction could enhance patient monitoring and treatment aftersurgery, direct patient treatment and decision making, and enhance participation in AKI interventional trials.